THE RELATIONSHIP OF TOTAL ORGANIC MATTER CONTENT IN SEDIMENTS WITH ABUNDANCE OF MACROZOOBNETOS IN THE MANGROVE AREA OF DESA ANAK SETATAH KEPUALAUAN MERANTI REGENCY RIAU PROVINCE - Octaviaty, Windy; Mulyadi, Aras; Nasution, Syafruddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT             This research was conducted in April 2019 with the aim to determine the abundance of macrozoobentos, the content of total organic sediment material and the relationship of total sediment organic matter to the abudance of macrozoobentos inte mangrove area of Anak Setatah Village. The determination of the sampling is purposive sampling. The results showed the highest value of macrozoobentos is 4,89 ind/m2. The highest average value of organic matter content in sediments is 13,71%. Simple linear regression analysis between abundance of macrozoobentos and total organic matter content of the sediment obtained by the equation y = 2,5462 + 0,1566x (r = 0,729).Key word : Mangrove, Macrozoobentos, Abundance, Organic of Sediment, Anak